Study on the influence of social media on the decline in smoking prevalence among adolescents - Rahman, Asep; Zuhrotunida , Zuhrotunida (Journal of Public Health Indonesian, 2025)
This study examines the influence of social media on reducing smoking prevalence among adolescents. Utilizing a quantitative approach with 220 respondents aged 12–18 years, the research highlights the significant role of social media in shaping attitudes and behaviors towards smoking. The findings reveal that anti-smoking campaigns on platforms like Instagram and TikTok effectively raise awareness of the health risks associated with smoking, leading to a decline in smoking prevalence. The study also identifies that visual and engaging content, along with community support, enhances the impact of these campaigns. However, the research acknowledges certain limitations, including the sample's regional focus and the absence of long-term impact analysis. This study contributes to the growing evidence of social media's potential as a public health intervention tool and offers practical insights for policymakers, educators, and health organizations to design targeted and effective campaigns.